Genome placement of alpha-haemolysin cluster is associated with alpha-haemolysin sequence variation, adhesin and iron acquisition factor profile of Escherichia coli. Issue 12 (23rd December 2021) - Kolenda, Rafał; Sidorczuk, Katarzyna; Noszka, Mateusz; Aleksandrowicz, Adrianna; Khan, Muhammad Moman; Burdukiewicz, Michał; Pickard, Derek; Schierack, Peter
Abstract : Since the discovery of haemolysis, many studies focused on a deeper understanding of this phenotype in Escherichia coli and its association with other virulence genes, diseases and pathogenic attributes/functions in the host. Our virulence-associated factor profiling and genome-wide association analysis of genomes of haemolytic and nonhaemolytic E. coli unveiled high prevalence of adhesins, iron acquisition genes and toxins in haemolytic bacteria. In the case of fimbriae with high prevalence, we analysed sequence variation of FimH, EcpD and CsgA, and showed that different adhesin variants were present in the analysed groups, indicating altered adhesive capabilities of haemolytic and nonhaemolytic E. coli . Analysis of over 1000 haemolytic E. coli genomes revealed that they are pathotypically, genetically and antigenically diverse, but their adhesin and iron acquisition repertoire is associated with genome placement of hlyCABD cluster. Haemolytic E. coli with chromosome-encoded alpha-haemolysin had high frequency of P, S, Auf fimbriae and multiple iron acquisition systems such as aerobactin, yersiniabactin, salmochelin, Fec, Sit, Bfd and hemin uptake systems. Haemolytic E. coli with plasmid-encoded alpha-haemolysin had similar adhesin profile to nonpathogenic E. coli, with high prevalence of Stg, Yra, Ygi, Ycb, Ybg, Ycf, Sfm, F9 fimbriae, Paa, Lda, intimin and type 3 secretion system encoding genes. Analysis of HlyCABD sequence variation revealed presence of variants associated with genome placement and pathotype.